Endocervical Chlamydia trachomatis infection in Canadian adolescents. - Hughes, E G (1989)
The highest prevalence rate of sexually transmitted chlamydial infection is among adolescent girls. To determine the rate among predominantly asymptomatic girls who were seen at a pediatric gynecology unit and to identify those at high risk we screened 541 such patients from Jan. 1 to Dec. 31, 1986, by means of direct fluorescent antibody testing; 422 (78.0%) were asymptomatic. The most common reason for presentation was a request for contraceptive advice (the reason for 59.2% of the patients). Of the 446 patients (82.4%) who were sexually active 66 (14.7%) had evidence of chlamydial infection; none of the 93 sexually inactive patients were infected. Neisseria gonorrhoeae was isolated from eight (1.5%) of the patients. The risk factors that correlated with chlamydial infection were abnormal vaginal discharge, abdominopelvic pain and an abnormal Papanicolaou test result. Because of the high morbidity rate associated with genital chlamydial infection and the high prevalence rate among adolescent girls, most of whom are asymptomatic, all sexually active teenagers should be screened.